Differentiation of apomictic and sexual genotypes of Brachiaria spp., using molecular markers - Pblete-Vargas, Jaime; Valadez-Moctezuma, Ernestina; García-de los Santos, Gabino; Martínez-Flores, Carlos; Peralta-Martínez, Armando (Ecosistemas y Recursos Agropecuarios, 2018)
Some species of Brachiaria are cultivated in the tropics because of their high productivity and drought resistance; their apomictic hybrids are of interest because of the almost null segregation and xation of the hybrid vigor in seeds. In this research, Amplied Fragment Length Polymorphism (AFLP) and Cleaved Amplied Polymorphic Sequence (CAPS) markers were used to dierentiate apomictic tetraploid and sexual diploid Brachiaria parents and their progeny. Polymorphism detected with AFLP was 91.3% and with CAPS 79.7%. Phenograms dierentiated each genotype and the clustering of parents and their progeny was by their degree of genetic relatedness. AFLP did not separate the apomictic genotypes from the sexual ones, but CAPS markers did so through the C15-8 marker. Some apomictic genotypes of the progeny inherited it from their B. ruziziensis sexual mother, which may be related to some segregating character of the parental line.